Optimal Operation and Control Design of DC Arrester for Renewable Energy Transmission - Feng, Yue; Li, Kaiping; Gao, Min; Liu, Yaozhang; Li, Xiaojun; Zhu, Jiawei (Frontiers in Energy Research, 2021)
The trip probability of transmission line under lightning stroke is rapidly increasing under complex weather conditions when large-scale renewable energy is intergrated with modern power grid. Line arrester plays a critical role in reducing lightning damage and economic losses, in which DC reference voltage is a critical parameter to evaluate line arresters. Hence, a set of on-site DC test system of transmission line arresters is developed to realize the DC reference voltage test in this article. The output DC voltage of the test system is continuously adjustable (0–200 kV), while its rated power and the maximum output current are set to 400 W and 2 mA, respectively. Furthermore, the system is powered by a lithium battery instead of a 220/380 V AC energy source. It employs split design and integrating assembly on-site that reduces the total weight by 36.7%, which considerably decreases the demand for the space of test site. Besides, the weights of control cabinet, multiplying cylinder, and energy source are reduced by 60, 54.55, and 33.33%, respectively. Meanwhile, the Bluetooth remote control module is used to effectively ensure the safety of test personnel. This system accomplishes DC reference voltage tests without removing line arresters on site, which can effectively enhance maintenance efficiency and economic benefits.